Identification of New Psychoactive Substances in Seized material Using UHPLC–QTOF-MS and An Online Mass Spectral Database. Issue 9 (30th March 2020) - von Cüpper, Maria; Dalsgaard, Petur Weihe; Linnet, Kristian
Abstract: The unpredictable pharmacological and toxicological effects associated with the recreational use of new psychoactive substances (NPS) represent a threat to the public health. Analysts are constantly facing a challenge to identify these designer drugs. In this article, five seized samples were submitted for analysis using ultra-high-performance liquid chromatography quadrupole time-of-flight mass spectrometry (UHPLC–QTOF-MS). To tentatively identify the NPS in the samples, the potential usage of an online mass spectral database (HighResNPS.com ) was explored by searching the exact mass of the precursor ion and evaluating the fragmentation profile. This approach successfully identified a suspected candidate compound present in three of the five samples. However, conclusive identification of the remaining two was not possible, due to indistinguishable fragmentation profiles of positional isomers. Therefore, complementary analytical methodologies are of paramount importance. In light of the above, HighResNPS.com is a useful tool in presumptively identifying an NPS without a reference standard.